THE EFFECT OF FINANCING RESTRUCTURATION POLICIES ON FINANCIAL AND FINANCING STABILITY OF SHARIA BANKING IN INDONESIA - Kurnia Dwi Sari Utami; Ahmad Fatoni; Elif Pardiansyah; Abdul Ghafar Ismail (Ekonomi Islam, 2023)
The purpose of this study is to analyze the effect of financing restructuring policies on the financial and credit stability of Islamic banks. The research period is from September 2018 to December 2020, using panel data from six Islamic banks in Indonesia. Based on chow, hausman, and lagrange multiplier tests, the random effect model was selected as the best estimation model. The findings show that inflation rate, bank size, and financing restructuring policy all have a negative and significant impact on financial stability. Meanwhile, GDP has a positive and significant effect on financial stability. In addition, credit stability shows that inflation and loan restructuring has a positive and significant impact on NPF.